Imagen y verdad - Ciudad, Mario (Revista Chilena de Humanidades, 2016)
This contributian is concerned with the conceptual problem of the logos. To this effect, Prof. Ciudad considers the relationship made by Husserl between his own image of Minerva and a philosophical system. Husserl’s propasitions are complemented with the Cartesian sense af methad in arder ta reach the mast simple by starting fram the mast camplex. In this way Praf. Ciudad comes to the secand part of the Discourse on Method, where a figurative expression of an anti-Minerva is found, the result of laborious science, reaffirmed by both Husserl and Brentano when they point out the ephemeral candition af the traditional systems. Together with the rational logos, there is a symbolic lagos, the latter providing the material for a logic of the figurative elements which lead to a dialectic of images as a tool far investigatian.